The Political Economy of Corruption and the Role of Financial Institutions - Kira Boerner; Christa Hainz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2006)
In many developing countries, we observe rather high levels of corruption. This is surprising from a political economy perspective, as the majority of people generally suffers from high corruption levels. We explain why citizens do not exert enough political pressure to reduce corruption if financial institutions are missing. Our model is based on the fact that corrupt officials have to pay entry fees to get lucrative positions. The mode of financing this entry fee determines the distribution of the rents from corruption. In a probabilistic voting model, we show that a lack of financial institutions can lead to more corruption as more voters are part of the corrupt system. Thus, the economic system has an effect on political outcomes. Well-functioning financial institutions, in turn, can increase the political support for anti-corruption measures.
urn:nbn:de:bvb:19-epub-13416-0
Keywords: D73; D72; O17; 330; Corruption; Financial Markets; Institutions; Development; Voting